Abu Nu‛aym Al-Iṣfahānī (d. 430/1038): Conflicting Opinions - Meis Al-Kaisi (Teosofia: Indonesian Journal of Islamic Mysticism, 2021)
Abu Nu‛aym al-Iṣfahānī (d. 430/1038) is a renowned figure with a glorious reputation. He is known as a hadith traditionist, historiographer, advocate of Sufism, and author of many works, the most celebrated of which is Ḥilyat al-awliyā’ wa-ṭabaqāt al-aṣfiyā’. Nonetheless, despite his glorious reputation, some scholars have criticized him and his renowned Ḥilya. Scholarship, in its turn, both classical and modern, has served Abu Nu‛aym no justice. Classical Arabic literature presents some information about his life and works in scattered short biographical entries. Modern scholarship has even less to offer in this regard. None of the existent sources presents a single biography that delivers a precise examination of Abu Nu‛aym’s status treating the opinions of both supporters and critics. This paper evaluates the conflicting opinions. It puts the puzzle pieces together to deliver a focused study of particular biographical details in Abu Nu‛aym’s life that examine the praise he has received from his proponents as well as the criticism from his opponents. This paper is the result of a project that assessed every available biographical entry on Abu Nu‛aym in both classical and modern literature to determine the different opinions on the scholar concerned. It delivers a list of all the literature that has a biographical mention of Abu Nu‛aym and that which has been examined for this study. This paper reveals that information about Abu Nu‛aym in primarily classical sources proved that criticism may be biased and religio-politically driven.